KODY I SEMANTYKI W KOMUNIKACJI ŚRODOWISK NACJONALISTYCZNYCH - Pielużek, Marcin (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Nationalistic groups employ numerous subculture communication channels to promote political programs, to manifest convictions and values, generating and reproducing specific communication codes. Purpose of the article is reconstruction of linguistic worldview of Polish nationalistic movements. Communication perspective assumed by the author is focused on construction methods and functions of respective constructs, performed based on key codes used in communication of the radical right-wing. Basing on constructivist theories, cognitive linguistics and concept of linguistic worldview, attempt of identification and analysis was undertaken with regard to basic identity codes and their semantics present in publications of extreme right-wing environments.